If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12=(2x+8)(4x-3)
We move all terms to the left:
12-((2x+8)(4x-3))=0
We multiply parentheses ..
-((+8x^2-6x+32x-24))+12=0
We calculate terms in parentheses: -((+8x^2-6x+32x-24)), so:We get rid of parentheses
(+8x^2-6x+32x-24)
We get rid of parentheses
8x^2-6x+32x-24
We add all the numbers together, and all the variables
8x^2+26x-24
Back to the equation:
-(8x^2+26x-24)
-8x^2-26x+24+12=0
We add all the numbers together, and all the variables
-8x^2-26x+36=0
a = -8; b = -26; c = +36;
Δ = b2-4ac
Δ = -262-4·(-8)·36
Δ = 1828
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{1828}=\sqrt{4*457}=\sqrt{4}*\sqrt{457}=2\sqrt{457}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-26)-2\sqrt{457}}{2*-8}=\frac{26-2\sqrt{457}}{-16} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-26)+2\sqrt{457}}{2*-8}=\frac{26+2\sqrt{457}}{-16} $
| -8-3d=d+12 | | 1/4(x−6)=21+4x | | 24+7f=66 | | -16t2+38.4t+3.5=0 | | -4v+2=38 | | x/12.4=54/75 | | 7x+23+10x-19=180 | | 22=9z | | p-78/2=7 | | 3x+7=5x-15(51) | | 4(y-15.1)+3=16.6 | | 4(y−15.1)+3=16.6 | | y-43/6=7 | | 3t=1.5t+24 | | 8^2x+6=8^4x-8 | | 7n+14-3n=4n-12 | | (4x)(5x+8)=0 | | 4x+10=6x=22 | | h-48/5=6 | | n+(n+1)+(n+2)+(n+3)=196 | | 17=1-4b | | 2c–4=5c-13 | | 6^8(x)=1296 | | 6a-7=5a-7a-15 | | -4+p/4=-3 | | -3(x-13.3)=-16.8 | | -15+3x-17x=-43 | | -12x-3x=36 | | m-91/2=3 | | -2-4p=5-5p | | 484=22f | | 10^(x)=10000 |